Pengaruh Metode Jigsaw terhadap Hasil Belajar IPA di Masa Pandemi COVID-19 - Mohammad Imam Sufiyanto; Aminatus Zahra (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The purpose of this study was to find out the influence of the application of jigsaw methods on student learning outcomes in fifth grade IPA subjects in SDN Bulay II District Galis Pamekasan Regency. This type of research is a quantitative approach or method, the method used is the queasy method of experimentation (pseudo experiment). The experimental design form in this study is the Non-equivalent Control Design Group. The population of the study is fifth Grade student class. While the data analysis techniques used are normality test, homogeneity, and hypothesis test. The results of the hypothesis test analysis for the results obtained show that t calculates the > t of the table with a significance level of 5% with a table t of 2,086. So the calculation > t table is 2,172 > 2,086, it can be concluded that Ho was rejected and Ha was accepted or there was an influence on the application of jigsaw methods on student learning outcomes on IPA subjects. The magnitude of the effect of the application of jigsaw methods on the learning outcomes, of students who use the effect size formula, obtained es of 1.06 which is included in the high criteria because ES > 1.00 which is 1.06 > 1.00. Students who use the effect size formula obtained ES of 1.06 which is included in the high criteria because ES > 1.00 this is 1.06>1.00. So that Ha is accepted and it can be concluded that the jigsaw method can have a positive influence with a high category on the learning outcomes of students of fifth grade IPA subjects in SDN Bulay II.